Nocturnal non-invasive positive pressure ventilation for COPD. (June 2015) - Windisch, Wolfram; Storre, Jan Hendrik; Köhnlein, Thomas
Abstract : There is an ongoing discussion on whether long-term non-invasive positive pressure ventilation (NPPV) should be used in chronic hypercapnic chronic obstructive pulmonary disease (COPD) patients. Early trials had failed to show convincing physiological and clinical effects using NPPV with assisted modes of ventilation and rather low inflation pressures. In particular, long-term survival could not be improved and findings on health-related quality of life had been conflicting. Remarkably, high-intensity NPPV using higher inflation pressures and back-up rates has recently been shown to be capable of improving blood gases, lung function, and health-related quality of life. Subsequently, a large study using this technique also showed a substantial improvement in the prognosis in these patients. Therefore, there is now increasing evidence to support physiologically effective NPPV in hypercapnic COPD patients, but how to best select patients still needs to be defined. The present article summarizes the physiological background and the current evidence on NPPV in COPD in addition to future considerations.